The state of human papillomavirus research in Africa - Kehinde Kazeem Kanmodi; Eyinade Adeduntan Egbedina; Jimoh Amzat; Kafayat Aminu; Lawrence Achilles Nnyanzi (Wiley, 2023)
Abstract Background Human papillomavirus (HPV) research scholarship evaluation is pivotal to the strategic planning, implementation and sustainability of HPV prevention and control programmes in Africa. Hence, this study evaluated HPV research scholarship in Africa. Methods This review-a bibliometric analysis-investigated the trends, patterns, dynamics and funding of HPV‐related literature production in Africa with a focus on the inequalities existing across thematic and subject areas, researchers, institutions and countries/territories/dependencies. The study data were obtained from SCOPUS database and analysed using the Microsoft Excel 2021 software. Result From 1974 (inception year) till 16 July 2022, a total of 2587 SCOPUS‐indexed literature on HPV were produced by African authors, with an average production rate of 50.5 publications per year (1974-2021). A few publications (1.2%) were in the Social Sciences. Most (95.1%) publications were in English, only a few (3.9%) were in French, whereas none was in Arabic, Portuguese, Spanish, Swahili or any other official language of the African Union. South Africa, Nigeria and Egypt were the three most prolific African countries. The 10 most prolific researchers were affiliated to public institutions in South Africa, Tanzania and Botswana. The top 10 funding sponsors were public institutions in the United States, the United Kingdom, Belgium and South Africa. Moreover, researchers and institutions affiliated to South Africa, Nigeria, Kenya and Uganda were the predominant beneficiaries. Only two indigenous journals made the list of top 10 journals publishing HPV research outputs from Africa. Conclusion Scholarly HPV research productivity in Africa is very low and worsened by multiple inequality gaps. There is an urgent need for equitably strengthening HPV research capacity in Africa.